TELAAH FEMINIST LEGAL THEORY DALAM KEBIJAKAN PEMBANGUNAN NASIONAL - Kuni Nasihatun Arifah; Dewi Novitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Feminist Legal Theory, as an analytical framework that focuses on the role of gender in law and policy, has become an important highlight in the context of national development policy. This research aims to investigate the contribution and application of Feminist Legal Theory in research and implementation of national development policies in Indonesia.Using an interdisciplinary approach, this research involves literature analysis, policy case studies, and interviews with relevant stakeholders. This research identifies gender issues in various aspects of national development, including access to education, health, employment and political participation.The research results highlight the role of Feminist Legal Theory in identifying and examining gender stereotypes in law and policy, as well as advocating for the need for policy change to achieve gender equality and social justice. This research also reveals the positive impact of a feminist perspective in changing policy orientation from a masculinity-based approach to an inclusive approach that pays attention to gender differences